Factors That Influence Menstrual Hygiene Behavior in Adolescents in Cipedes Village, Tasikmalaya City - Neni Neni; Yuldan Faturahman; Iseu Siti Aisyah (Jurnal Penelitian Pendidikan IPA, 2025)
Adolescence is an important period in the individual development process, marked by various biological, psychological, and sexual changes. Menstruation (menarche) is one of the early characteristics for adolescent girls that indicates the functioning of the reproductive system. This condition requires attention to the cleanliness of intimate organs, because the shedding of the endometrium which is rich in blood vessels can increase the risk of infection. Lack of implementation of good menstrual hygiene practices can have an impact on the health of the reproductive tract. Objective: To review the importance of implementing hygiene during menstruation as part of efforts to protect the reproductive health of adolescent girls and prevent infection. Menstrual hygiene includes actions to maintain cleanliness such as choosing the right sanitary napkins, changing them regularly, and cleaning female organs in the right way. Lack of education and information about hygiene management during menstruation is one of the factors that influences this poor practice. Social, cultural factors, as well as individual values and habits also play a role in shaping menstrual hygiene behavior. Counseling and education about menstrual hygiene play an important role in supporting the reproductive health of adolescent girls. Digital media such as Android applications can be used as an effective educational tool to improve understanding and healthy behavior during menstruation.